(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Klippel-Fiel syndrome (KFS) is a rare congenital disorder characterized by the presence of a triad of short neck, limited neck mobility, and low posterior hairline. A 5-year-old girl of consanguineous parents had limited neck movement and poor growth for three years. Her height was 87cm (SDS -4.6), and her weight was 11kg (SDS-2.8), indicating significant growth retardation. Intelligence was normal for age, but a clinical examination revealed a short neck, limited neck movement, and Sprengel deformity. Although her thyroid function was normal, the growth hormone stimulation test (using clonidine) was borderline low. By karyotyping, a normal female pattern (46, XX) was identified. While the echocardiogram was normal, the ultrasound revealed that the left kidney was absent, along with an infantile uterus. An X-ray of the cervical spine revealed a Sprengel deformity and cervical ribs. Her radiological bone age was delayed. The diagnosis of Klippel-Feil Syndrome was made by using clinical presentation, physical examination, and laboratory investigations. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S59]